PENGARUH ENVIRONMENTAL SOSIAL GOVERNANCE (ESG) REPORTING TERHADAP TOBIN’S Q PADA SEKTOR JASA DI BEI - Saraswati, Wiwik; Hadiyatno, Didik; Tangke Rante, Nely; Rama Pramudia, Dimas (Fakultas Ekonomi Universitas Balikpapan, 2025)
This research is based on the change towards a green economy in Indonesia where companies are not only thinking about profits, but also to increase transparency related to Environmental, Social, and Governance (ESG) aspects. The results of the study show that ESG disclosure serves as an effective positive signal to reduce information inequality between companies and stockholders. This research is on the services sector during the 2023-2025 period, where consistent ESG implementation has the potential to increase the market value of companies (Tobin's Q). Investors tend to give higher ratings to companies that demonstrate a commitment to sustainability, as they are perceived to have better risk resilience in the face of changing regulations and global demands.